Prototype development of mecanum wheels mobile robot: A review - Abd Mutalib, Mohd Azri; Azlan, Norsinnira Zainul (Universitas Muhammadiyah Surakarta, 2020)
This paper provides the review and prototype development of mecanum wheels mobile robot (MWMR). Nowadays, there is a high market demand for a wheeled machine or wheeled robot for various applications. The ability to move in any direction without altering even a single wheel makes this type of wheel useful for driving, especially in a narrowed or confined space. Various styles of implementing MWMR are discussed in this paper. The kinematic derivation and dynamic modelling are also presented. Characteristically, mecanum wheels face traditional mobile application issues like jerking and slippage, contributing to low positioning accuracy and repeatability. Besides, environmental factors like disturbance and uncertainty also contribute to these issues. The control strategies in previous research have been reviewed and presented in this paper to reduce the effect. Finally, a low-cost prototype of MWMR was developed as an experimental platform for future study.